2018
DOI: 10.3126/nmj.v1i1.20394
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors Among Medical Students

Abstract: Introduction:Refractive errors are becoming a problem in many societies, with prevalence rates of myopia in many Asian urban countries reaching epidemic proportions. This study aims to determine the prevalence rates of various refractive errors among medical students of Kist Medical College Teaching Hospital, Nepal. Materials and Methods:Medical students were included in the study. Demographic data was obtained via questionnaires filled in by the students after taking informed verbal consent. Refractive error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In this study, the prevalence of refractive errors was 45.1%, with myopia having the highest prevalence (59%); furthermore, studies done among medical students in Nepal, Singapore, and Taiwan diagnosed them to have refractive errors with myopia scoring 64.81%, 89.6%, and 92.8%, respectively [18,19]. All studies agreed that myopia is the most common form of refractive error among medical students, the increasing rates of myopia among medical students could be due to near work tasks and computer use [20].…”
Section: Discussionmentioning
confidence: 49%
“…In this study, the prevalence of refractive errors was 45.1%, with myopia having the highest prevalence (59%); furthermore, studies done among medical students in Nepal, Singapore, and Taiwan diagnosed them to have refractive errors with myopia scoring 64.81%, 89.6%, and 92.8%, respectively [18,19]. All studies agreed that myopia is the most common form of refractive error among medical students, the increasing rates of myopia among medical students could be due to near work tasks and computer use [20].…”
Section: Discussionmentioning
confidence: 49%
“…8 In our study, the prevalence of myopia was 42.65%, among the 279 medical students, which was lower in comparison to prevalence studies done on medical students in our geographic region. 10,11 In similar studies conducted on medical students, the prevalence of myopia was 64.81%, 10 in Nepal, 52.78% in India, 11 and 47% in Pakistan. 12 The Raine study which was conducted in Australia reported the prevalence of myopia in young adults between the age of 20 to 28 years as 25.8% to 33.2%, 13 which is lower compared to our study.…”
Section: Discussionmentioning
confidence: 84%
“…The occurrence of vision problems among medical students has been documented to range from 21.4% to 59.5% in various countries. Specifically, in Pakistan, the prevalence is reported as 59.5% [8], while in India it is 49.6% [9], Saudi Arabia 48.8% [10], Iraq 33.3% [11], Malaysia 32.2% [12], and Nepal 21.4% [13]. Unfortunately, we are unable to provide the prevalence of refractive errors in our study since we did not conduct refraction tests or subjective corrections to determine the specific type and severity of vision problems among the students.…”
Section: Discussionmentioning
confidence: 99%